Language Choice and Vitality of Satun Malay Dialect in the Family Domain in Muang Satun District, Thailand: A Domain Analysis (Jurnal Bahasa, 2025)
Satun, which borders the state of Perlis in northern Peninsular Malaysia, is a major tourism destination for visitors from around the world, including those from Malaysia. Language is among the factors that attract Malaysian tourists. However, previous studies indicate that the local variety, the Satun Malay dialect (DMS), has begun to exhibit tendencies toward language shift. Therefore, this study was conducted to identify language choice and to analyse the vitality level of DMS among 124 tourism product workers (PPP) in the Muang Satun district, with the aim of examining whether employment (in the tourism sector) influences language choice in the family domain. The study is grounded in Fishman’s (1972) domain analysis and UNESCO’s Language Vitality and Endangerment (LVE) Framework (2011). Data were analysed through cross-tabulations using the Statistical Package of Social Sciences (SPSS) version 27 software to obtain the percentage distribution of language choices across age groups, followed by triangulation using the LVE (2011) framework to determine the level of language vitality. The findings, based on the percentage of PPP’s language choices, reveal that DMS was at level 4, which is stable yet threatened as it continues to be moderately used among older and adult speakers, but is declining among young speakers across all examined subdomains. This suggests that the use of DMS by PPP in the family domain is beginning to display features of language shift. Hence, PPP are encouraged to take appropriate measures to ensure that DMS is preserved and transmitted to future generations.Keywords: Language choice, age group, tourism product workers, Satun Malay Dialect (DMS), language vitality, language shiftFull Text: PDF